Mitigation of Salinity Stress in Plants by Arbuscular Mycorrhizal Symbiosis: Current Understanding and New Challenges - Evelin, Heikham; Devi, Thokchom Sarda; Gupta, Samta; Kapoor, Rupam (Frontiers in Plant Science, 2019)
Modern agriculture is facing twin challenge of ensuring global food security and executing it in a sustainable manner. However, the rapidly expanding salinity stress in cultivable areas poses a major peril to crop yield. Among various biotechnological techniques being used to reduce the negative effects of salinity, the use of arbuscular mycorrhizal fungi (AMF) is considered to be an efficient approach for bio-amelioration of salinity stress. AMF deploy an array of biochemical and physiological mechanisms that act in a concerted manner to provide more salinity tolerance to the host plant. Some of the well-known mechanisms include improved nutrient uptake and maintenance of ionic homeostasis, superior water use efficiency and osmoprotection, enhanced photosynthetic efficiency, preservation of cell ultrastructure, and reinforced antioxidant metabolism. Molecular studies in past one decade have further elucidated the processes involved in amelioration of salt stress in mycorrhizal plants. The participating AMF induce expression of genes involved in Na+ extrusion to the soil solution, K+ acquisition (by phloem loading and unloading) and release into the xylem, therefore maintaining favorable Na+ : K+ ratio. Colonization by AMF differentially affects expression of plasma membrane and tonoplast aquaporins (PIPs and TIPs), which consequently improves water status of the plant. Formation of AM (arbuscular mycorrhiza) surges the capacity of plant to mend photosystem-II (PSII) and boosts quantum efficiency of PSII under salt stress conditions by mounting the transcript levels of chloroplast genes encoding antenna proteins involved in transfer of excitation energy. Furthermore, AM-induced interplay of phytohormones, including strigolactones, abscisic acid, giberellic acid, salicylic acid, and jasmonic acid have also been associated with the salt tolerance mechanism. This review comprehensively covers major research advances on physiological, biochemical, and molecular mechanisms implicated in AM-induced salt stress tolerance in plants. The review identifies the challenges involved in the application of AM in alleviation of salt stress in plants in order to improve crop productivity.